Conflict and consensus in stakeholder attitudes toward sustainable transport projects in China: An empirical investigation. (April 2016) - Wei, Hsi-Hsien; Liu, Muqing; Skibniewski, Mirosław J.; Balali, Vahid
Abstract: Conflicts inevitably occur in major transport projects as various stakeholders express diverse, often conflicting needs and concerns, and failing to address and manage these conﬂicts often leads to project failures. Understanding stakeholders' perceptions and the discrepancies among them is crucial to an effective dialogue among the parties seeking to build consensus. This study investigates the potential influences of stakeholder characteristics as well as project environments on conflicts and consensuses in stakeholders' overall preferences about sustainable transport projects. Data on the perspectives of three stakeholder-group types (system providers, project designers, and system users) with regard to 14 sustainability criteria are drawn from a survey of eight major transport projects across China. Two-way analysis of variance is then carried out to investigate whether or not the differences in the mean scores among stakeholder-group types and cities were statistically significant. The results show that discrepancies of opinion about transport-project sustainability criteria prevail among stakeholder-group types in every region we studied, due to these types' different needs and concerns. Our findings also suggest that special attention should be given to cases in which multiple stakeholder groups assign the same priorities to certain criteria, as those criteria are likely to represent the most serious issues affecting all stakeholders in a given project environment. With regard to the potential influences of project environments, we found that, in general, the discrepancies in stakeholders' prior concerns about sustainability criteria exhibited no obvious geographic pattern. However, exceptions did occur when a specific criterion was of major concern in a given project environment. Taken together, our findings emphasize the necessity of addressing and managing specific local issues, and the divergent concerns of stakeholders, when planning sustainable-transport projects. Highlights: The influences of stakeholders and project environments on conflicts in sustainable transport are investigated. Discrepancies of opinion about sustainability criteria prevail among stakeholder groups due to different needs and concerns. Special attention should be given to cases in which multiple stakeholders assign the same priorities to certain criteria. Discrepancies in stakeholders' concerns about sustainability criteria exhibited no obvious geographic pattern.